Digital Disaster Crisis Management: Examining the Influence of Mobile Technology and Organizational Effectiveness on Disaster Governance - Helen Dias Andhini; Abdul Rahman Kadir; Muhammad Yunus Amar; Nohong, Mursalim; Suhaily Sudarman, (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study examines how mobile technology acceptance and organizational efficacy influence crisis information sharing and how this sharing affects disaster response effectiveness and governance quality. Using a quantitative cross-sectional design, data were collected from 285 Indonesian disaster response personnel and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that technology acceptance (β = 0.34, p < 0.001) and organizational efficacy (β = 0.41, p < 0.001) significantly promote information sharing. Information sharing, in turn, positively impacts response effectiveness (β = 0.52) and governance quality (β = 0.58). However, mediation analysis indicates that information sharing does not mediate all relationships; specifically, it does not mediate the link between technology acceptance and governance quality nor between organizational efficacy and tactical response effectiveness. The model accounts for up to 51% of the variance in governance outcomes. These findings offer a nuanced perspective for disaster management theory, highlighting that while digital tools are important catalysts, they must be integrated with institutional capacity and structured governance to ensure shared information leads to improved disaster outcomes.